Network visualization for outbreak response: Mapping the Ebola Virus Disease (EVD) chains of transmission in N'Zérékoré, Guinea. Issue 3 (March 2017) - Valencia, C.; Bah, H.; Fatoumata, B.; Rodier, G.; Diallo, B.; Koné, M.; Giese, C.; Conde, L.; Malano, E.; Mollet, T.; Jansa, J.; Coulombier, D.; et al.
Summary: Background: During the 2014–2015 Ebola Virus Disease (EVD) outbreak in N'Zérékoré, Forested Guinea, modes of transmission remained unexamined for a number of new cases. We used network visualization to investigate EVD transmission chains (TC) in seven sub-prefectures of N'Zérékoré in order to adapt outbreak response. Methods: Between August 2014 and February 2015, the EVD outbreak response team including the World Health Organization (WHO) and local health authorities routinely collected information among new cases regarding hospital visits, cases within a household, participation in burials, as well as dates of symptom onset, serial intervals (SI) and exposure to EVD. SI's were defined as the interval between symptom onset in an index case and symptom onset in a secondary case infected by that index case. Cases who reported hospital visits, contact with a case in the household or participating in burials were attributed to these exposures. Results: We identified seven TC (two urban and five rural) gathering characteristics of 109 probable/confirmed cases. Overall, 61% (66 cases, SI range: 7–20 days) were household related, 32% (35 cases, SI range 8–30 days) were household or burial related and 7% (8 cases, SI range: 4–20 days) were hospital-related. In the urban chains (18 cases, SI range: 7–20 days), 12 cases were household related and 6 cases were hospital related, none where household or burial related. In the rural chains (84 cases, SI range: 7–30 days), 60% (50 cases) were household related, 1% (1 case) was hospital related and 39% (34 cases) were household or burial related. No cases reported multiple exposures. Conclusions: Network visualization during field response is crucial in enhancing local control strategies, refining outbreak response and aiding rapid response teams in insuring psychosocial and socio-economic recovery. Urban settings need to focus on reducing hospital EVD transmission whereas rural settings should focus on raising awareness of transmission within a household and safeguarding EVD burials. Highlights: Include network analysis into outbreak response activities. Monitoring chains of person-to person transmission optimize local control strategies. Improve surveillance of Ebola virus disease (EVD) and collection of exposure data. Serial intervals exceeding 21-days incubation suggest intermediary hosts. Whole genome sequencing (WGS) can aid chain of transmission mapping.